cAMP Signaling Regulates Synchronised Growth of Symbiotic Epichloë Fungi with the Host Grass Lolium perenne - Voisey, Christine R.; Christensen, Michael T.; Johnson, Linda J.; Forester, Natasha T.; Gagic, Milan; Bryan, Gregory T.; Simpson, Wayne R.; Fleetwood, Damien J.; Card, Stuart D.; Koolaard, John P.; Maclean, Paul H.; Johnson, Richard D. (Frontiers in Plant Science, 2016)
The seed-transmitted fungal symbiont, Epichloë festucae, colonizes grasses by infecting host tissues as they form on the shoot apical meristem (SAM) of the seedling. How this fungus accommodates the complexities of plant development to successfully colonize the leaves and inflorescences is unclear. Since adenosine 3′, 5′-cyclic monophosphate (cAMP)-dependent signaling is often essential for host colonization by fungal pathogens, we disrupted the cAMP cascade by insertional mutagenesis of the E. festucae adenylate cyclase gene (acyA). Consistent with deletions of this gene in other fungi, acyA mutants had a slow radial growth rate in culture, and hyphae were convoluted and hyper-branched suggesting that fungal apical dominance had been disrupted. Nitro blue tetrazolium (NBT) staining of hyphae showed that cAMP disruption mutants were impaired in their ability to synthesize superoxide, indicating that cAMP signaling regulates accumulation of reactive oxygen species (ROS). Despite significant defects in hyphal growth and ROS production, E. festucae ΔacyA mutants were infectious and capable of forming symbiotic associations with grasses. Plants infected with E. festucae ΔacyA were marginally less robust than the wild-type (WT), however hyphae were hyper-branched, and leaf tissues heavily colonized, indicating that the tight regulation of hyphal growth normally observed in maturing leaves requires functional cAMP signaling.